Is early percutaneous coronary intervention safe in patients ACS and cancer?. (14th October 2021) - Scarpone, M; Bergami, M; Cenko, E; Vasiljevic, Z; Zdravkovic, M; Vavlukis, M; Kedev, S; Milicic, D; Manfrini, O; Bugiardini, R
Abstract: Background: Patients with malignancies may have a high pro-thrombotic status as well as a high risk of hemorrhagic events either due to the tumor or its treatment. For this reason, these patients have always been excluded from randomized clinical trial on percutaneous coronary intervention (PCI). Aim: To investigate the safety of PCI in patients with malignancies admitted for an AMI. Methods and results: Retrospective analysis on an international European ACS registry. Primary endpoint: in-hospital mortality. Secondary endpoint: periprocedural-complications. There were 273 patients (35% women) with AMI and malignancies. Colon (19%), prostate (14%), breast (13%), lung (8%) and blood (8%) malignancies were the most frequents type of cancer. Women and men had similar age (68±11.5 vs 69.1±11.5, p=ns). STEMI was in 56% of patients (with no significant gender difference: 51% men vs 65% women, p=0.09). PCI was performed in 64% of patients (with primary PCI in 75% of STEMI). The rate of complications during cardiac catheterization and intervention was 6.5% (2.1% distal embolization, 2.1% no-reflow, 0.7% acute closure, 0.7% dissection, 0.7% perforation, none major bleeding). Nobody among patients that had cardiac catheterization and intervention complications died during hospital stay. In-hospital mortality was 5.9%. The group of patients treated with PCI had a significantly lower rate of death then that of those treated non invasively (1.7% vs 13.1%, p<0.ehab724.28851). Factors associated with lower probability to receive cardiac catheterization were older age (OR: 0.94, 95% CI: 0.92–0.97) and absence of typical chest pain at admission (OR: 0.38; 95% CI: 0.18–0.81), but the type of malignancy and gender were not. On multivariable model, age (OR: 1.1, 95% CI: 1.03–1.17) and PCI (OR: 0.16, 95% CI: 0.04–0.59) were independently associated with the risk of in-hospital death for ACS (increased and decreased risk, respectively). Conclusion: These preliminary data from real word support the safety use of PCI in patients with malignancies and ACS, which have always been excluded from randomized clinical trial. Funding Acknowledgement: Type of funding sources: None.